First Report of Clavinema mariae (Nematoda: Philometridae) in Cultured Rockfish, Sebastes schlegeli, in Cheonsuman (Bay), the Republic of Korea - Han, Hyun-Ja; Seo, Jung Soo; Park, Jeong Su; Lee, Haeng Lim; Seo, Han Gill; Jung, Sung Hee; Kwon, Se Ryun (Korean journal of parasitology, 2017)
In July 2012, philometrid nematodes were discovered in cultured rockfish ( ) in Cheonsuman (Bay), the Republic of Korea. The nematodes were detected in the epithelial tissues of the rockfish and were identified as based on morphological studies using light and scanning electron microscopy. They revealed the characteristics same as previously identified , notably having a long body with narrow posterior half, no caudal projection, a cylindrical-shaped esophagus, a well-developed anterior bulbous part of the esophagus, cephalic papillae, and a dorsal esophageal gland. This is the first confirmation of infection in rockfish in Korea.